Le boys club - Delvaux, Martine (Les éditions du remue-ménage, 2019)
"Ils sont tournés les uns vers les autres. Ils s'observent et s'écoutent. Ils s'échangent des idées, des armes, de l'argent ou des femmes. Dans cet univers clos réservé aux hommes, le pouvoir se relaie et se perpétue à la façon d'une chorégraphie mortifère. Le boys club n'est pas une institution du passé. Il est bien vivant, tentaculaire : État, Église, armée, université, fraternités, firmes... et la liste s'allonge. À la manière d'une chasse à l'image, c'est dans les représentations au cinéma et à la télévision que Martine Delvaux le traque. Véritable plongée en eaux noires, ce livre nous invite à considérer l'entre-soi des hommes comme un phénomène régressif. Un dispositif à profaner, déconstruire, refuser, parce que nos vies comptent"--Page 4 de la couverture.
Keywords: approches et analyses; arts; cours; discipline; discours dominant; fem1000; fem1300; premier cycle; privilèges; sexisme; systèmes d'oppressions; thématiques; violences; études culturelles; études littéraires

Racializing heterosexuality: Non-normativity and East Asian characters in James Bond films - Hiramoto, Mie; Pua, Phoebe (Language in Society, 2019)
This article investigates how naturalized models of hegemonic masculinity affect race and sexuality in the James Bond film series. Through close analysis of film dialogue and paralinguistic cues, the article examines how the sexualities of East Asian female and male characters are constructed as oversexed and undersexed, respectively. The analysis therefore affirms Connell's (1995) conception of white heterosexual masculinity as exemplary: East Asian characters are positioned not only as racial Others, but as bodies upon which Bond's heterosexual masculinity is reflected and affirmed as normative and, by extension, ideal. In this way, race is curiously invoked to ‘explain’ sexuality, and Bond's unmarked white masculinity becomes the normative referent for expressions of heterosexual desire. By showing how the sexuality of East Asian characters is typecast as non-normative, the article gestures toward the possibility of theorizing racialized performances of heterosexuality as queer.
Keywords: approches et analyses; arts; arts visuels et médiatiques; asie; asie de l'est; cinéma; cours; discipline; identités de genre; intersectionnalité; lin2685; patriarcat; pol5480; premier cycle; privilèges; racisme; ressource en ligne; régions géographiques; systèmes d'oppressions; études de genres

Peau: à propos de sexe, de classe et de littérature - Allison, Dorothy.. (Sorcières, 2015)
Activiste féministe lesbienne radicale depuis les années 1970, Dorothy Allison a connu le succès avec ses romans (L’Histoire de Bone, Retour à Cayro). En 1994, elle publie Peau, un recueil d’essais. Elle y parle de son enfance, d’inceste, de lesbophobie. Elle raconte son engagement féministe, sa sexualité, les « Sex Wars » des années 1980. Elle partage ses réflexions sur la littérature : comment écrire l’extrême misère sociale, comment écrire sur le sexe ? Un livre tout à la fois intime, décapant et profondément politique, réédité avec sept textes inédits en français.
Keywords: amériques; approches et analyses; arts; cours; discipline; discours dominant; fem1300; histoire et politique; lesbianisme; militance; personnes lesbiennes; premier cycle; privilèges; régions géographiques; sexualité; systèmes d'oppressions; thématiques; travail du sexe; états-unis; études littéraires

This bridge called my back: Writings by radical women of color - Moraga, Cherríe; Anzaldúa, Gloria (SUNY Press., 2015)
merged in the last quarter of the twentieth century. Through personal essays, criticism, interviews, testimonials, poetry, and visual art, the collection explores, as coeditor Cherríe Moraga writes, the complex confluence of identities--race, class, gender, and sexuality--systemic to women of color oppression and liberation. Reissued here, forty years after its inception, this anniversary edition contains a new preface by Moraga reflecting on Bridge's living legacy and the broader community of women of color activists, writers, and artists whose enduring contributions dovetail with its radical vision. Further features help set the volume's historical context, including an extended introduction by Moraga from the 2015 edition, a statement written by Gloria Anzaldúa in 1983, and visual art produced during the same period by Betye Saar, Ana Mendieta, Yolanda López, and others, curated by their contemporary, artist Celia Herrera Rodríguez. Bridge continues to reflect an evolving definition of feminism, one that can effectively adapt to and help inform an understanding of the changing economic and social conditions of women of color in the United States and throughout the world.
Keywords: 1900-1999; amériques; anthologie; approches et analyses; arts; cours; cycles supérieurs; discipline; fem1000; fem7000; femmes* de couleur; histoire et politique; intersectionnalité; lit3220; littérature; pol4212; pratiques féministes; premier cycle; privilèges; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; témoignage; états-unis; études littéraires